2018
DOI: 10.1177/1687814018754674
|View full text |Cite
|
Sign up to set email alerts
|

Improved multi-wavelet denoising with neighboring coefficients of cutting force for application in the load spectrum of computer numerical control lathe

Abstract: To obtain accurate computer numerical control lathe cutting force signals and improve the precision of load stress cycle statistic, an improved multi-wavelet denoising with neighboring coefficients method is proposed. First, statistical variance smoothing is applied to remove the singular points in the original signal. The processed signal is then denoised with the multi-wavelet with neighboring coefficients method. Second, based on the change laws of the correlation dimension and the values of Brock, Dechert,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Kim [ 75 ] used the time–frequency image obtained via short-time Fourier transform as the input signal of an ANN classifier and then applied the neural network classifier to identify different impact noises, distinguishing the actual fault impact noise from the background noise with an accuracy of 100%. He [ 76 ] proposed an improved multiwavelet signal processing method with adjacent coefficients and proved that this method can effectively suppress the interference of high-frequency noise on the target signal.…”
Section: Noise Signal Acquisition and Numerical Analysis And Noise Co...mentioning
confidence: 99%
“…Kim [ 75 ] used the time–frequency image obtained via short-time Fourier transform as the input signal of an ANN classifier and then applied the neural network classifier to identify different impact noises, distinguishing the actual fault impact noise from the background noise with an accuracy of 100%. He [ 76 ] proposed an improved multiwavelet signal processing method with adjacent coefficients and proved that this method can effectively suppress the interference of high-frequency noise on the target signal.…”
Section: Noise Signal Acquisition and Numerical Analysis And Noise Co...mentioning
confidence: 99%
“…The relationship (17) links the filters C(z) and D(z) to the polyphase filter H p (z). Differentiation after multiplication by any constant vector v gives:…”
Section: Vanishing Moment Conditions For Multiwaveletsmentioning
confidence: 99%
“…Multiwavelets are more flexible, and can combine properties such as compact support, orthogonality and symmetry. This added flexibility is for example advantageous in multiwavelet denoising, which has been applied in rolling bearing fault detection [13][14][15][16], and in the load spectrum of computer numerical control lathe [17]. Recently, the correspondence between multiwavelet shrinkage and nonlinear diffusion was studied [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tool wears can also make an influence on the cutting force. It is shown that instantaneous milling force can be predicted with the model that comprised the relationship between milling force against tool flank wear ( Zhu and Zhang, 2019). The energy consumption assessment for machining system through models has potential applications in complex production environments those are usually broken up into constant no-load loss, cutting energy loss and auxiliary energy loss.…”
Section: Introductionmentioning
confidence: 99%